Neoliberalizing Educational Reform: America’s Quest for Profitable Market-Colonies and the Undoing of Public Good - Sturges, Keith M (Springer, 2016)
“In this era, when ‘commonsense’ in educational discourse is so deeply framed by neoliberalism, we must better understand both the uniquely situated and the insidiously interconnected nature of so-called reforms. Thank you to Keith M. Sturges and colleagues for illuminating exactly this in their important and hard-hitting new book that reveals not merely how neoliberal reforms are designed to reinforce inequity, but also how the contradictions within provide ample opportunity to collectivize and act with hope.” – Kevin Kumashiro, author of Bad Teacher!: How Blaming Teachers Distorts the Bigger Picture “In this important volume, editor Keith M. Sturges has taken the most useful discussions of neoliberalism and – with great precision, clarity and utility – seen them applied to the education arena. Over 13 chapters, leading education thinkers lay bare sets of realities that the broader public, school administrators, and policy makers would do well to fully understand. These range from the impact of neoliberal thinking upon chartering, parent involvement, teacher training, school climate, funding and more. I’ll be using the chapters in this text in a variety of ways. They’ll inform conversations with local, state and federal policy makers, and inform conversations with school leaders and district leaders. I’ll also be assigning the text in my graduate seminar on education policy. Finally, the chapters will inform several lectures in my undergraduate class on ‘The Promise and Peril of Public Education.’ What a gem of a volume!” – Kevin Michael Foster, Executive Director, The Institute for Community, University and School Partnerships (ICUSP)